Speech by the Chairperson of the University of Embu Endowment Fund Board of Management Hon. Lenny Kivuti on the occasion of Launch of the University of Embu Endowment Fund held at The University of Embu on Thursday, 25th October 2018. - Kivuti, Lenny (University of Embu, 2018)
Speech by the Chairperson of the University of Embu Endowment Fund Board of Management Hon. Lenny Kivuti on the occasion of Launch of the University of Embu Endowment Fund held at The University of Embu on Thursday, 25th October 2018.